2016
DOI: 10.1007/s10661-016-5314-3
|View full text |Cite
|
Sign up to set email alerts
|

Toxic heavy metals in sediments, seawater, and molluscs in the eastern and western coastal waters of Guangdong Province, South China

Abstract: Heavy metal concentrations and distribution were studied in sediments, seawater, and molluscs, and the possible heavy metal sources in the coastal waters of Guangdong Province, South China were discussed. The results showed that the concentrations of Cu, Pb, Zn, and Cr in sediments in eastern coastal waters were generally higher than those in the western coastal waters. However, concentrations of most metals in seawater and molluscs in western waters were higher than in the eastern waters, which was tightly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Sea cucumbers are species of echinoderm with mucous skin, which can potentially accumulate heavy metals by absorption from the polluted sediments in the sea (Luo et al, 2010;Wang et al, 2015;Zhang et al, 2016). The consumption of the sea cucumbers containing high level of heavy metals may potentially cause serious negative impacts on health, since they are persistent, bioaccumulative and toxic (King et al, 2010;Nghia et al, 2009;Noël et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Sea cucumbers are species of echinoderm with mucous skin, which can potentially accumulate heavy metals by absorption from the polluted sediments in the sea (Luo et al, 2010;Wang et al, 2015;Zhang et al, 2016). The consumption of the sea cucumbers containing high level of heavy metals may potentially cause serious negative impacts on health, since they are persistent, bioaccumulative and toxic (King et al, 2010;Nghia et al, 2009;Noël et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Zhelin Bay in the Shantou area is an intensive mariculture area. Therefore, industrial and agricultural wastewater is an important source of metals in the area [ 13 ]. In addition, Hanjiang, as the second largest river in Guangdong Province, flows through the Chaoshan Plain and important industrial cities, such as Chaozhou and Jieyang, and into the South China Sea in Shantou City as the source, bringing a large number of pollutants to the coastal area [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, industrial and agricultural wastewater is an important source of metals in the area [ 13 ]. In addition, Hanjiang, as the second largest river in Guangdong Province, flows through the Chaoshan Plain and important industrial cities, such as Chaozhou and Jieyang, and into the South China Sea in Shantou City as the source, bringing a large number of pollutants to the coastal area [ 13 ]. In addition to the reasons noted above, the large loss of coastal wetlands in Guangdong is also an important reason for the accumulation of heavy metals in the ocean, especially in the bay wetlands, which have an extremely strong self-purification capacity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the coastal waters of the surrounding South China Sea, the overall quality of Jieshi Bay sea sediment is good (Liu et al, 2012;Wang et al, 2013;Zhang et al, 2015;Zhang et al, 2016;Wang et al, 2022;Zhang et al, 2022). We found that most of the heavy metal contents in the surface sediment was at the medium level, though the Hg and Zn contents were comparatively high in some sea areas.…”
Section: Distribution and Risk Assessment Of Hms In Sedimentmentioning
confidence: 99%